Gambaran Histologi Pankreas Tikus Wistar yang diberi Ekstrak Daun Kelor (Moringa Oleifera) setelah diinduksi Aloksan - Jonathan Alexander Utama; Martha Marie Kaseke; Elvin Clara Angmalisang (Syntax Idea)
Diabetes mellitus is a metabolic disorder with a steadily increasing global prevalence, significantly affecting pancreatic function. Moringa leaf (Moringa oleifera) extract has potential antioxidant and antidiabetic properties, yet its effects on the pancreas after alloxan induction remain underexplored. This study aimed to see the histological features of the pancreas in Wistar rats administered Moringa leaf extract at various doses (100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW) for 14 days post-alloxan induction. This laboratory experimental study involved 25 Wistar rats. The rats were divided into five experimental groups. The experimental groups are induced with alloxan at a dose of 170 mg/kgBW to create a hyperglycemic condition.. Group A served as a negative control, Group B was a positive control administered glibenclamide (0.09 mg/200 gBW), while Groups C, D, and E received Moringa leaf extract at doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW, respectively, for 14 days. Histological examination revealed six islets of langerhans in the normal group. Group A showed two islets, Group B showed 13, Group C showed eight, Group D showed four, and Group E showed 11. The administration of Moringa oleifera leaf extract to alloxan-induced Wistar rats demonstrated a protective effect against pancreatic damage, with each group showing varying degrees of histological improvement.